Role of glutathione S-transferases and monoamine oxidase in the detoxification of Pomacea canaliculata exposed to tea saponin - Yanhui Lu; Haitao Lu; Xusong Zheng; Hongxing Xu; Zhongxian Lu (Ecotoxicology and Environmental Safety)
Pomacea canaliculata is one of the most destructive threats to the safe production of rice. Molluscicides are the primary measure for controlling this pest species. Tea saponin (TS) is a plant secondary metabolite with a high snail-killing activity. However, some individuals have enhanced detoxification metabolism against TS, leading to a weakened control efficiency of TS to P. canaliculata. To clarify the detoxification and metabolic mechanisms of TS in P. canaliculata, we characterized the toxicity of TS against the snails. Additionally, we examined its biochemical and molecular effects on glutathione S-transferases (GSTs) and monoamine oxidase (MAO) activities, as well as their corresponding gene expression levels. The results showed that the LC50 values were 6.12, 9.03, and 9.35 mg/L for small, medium, and large snails following 24 h exposure. The LT50 values were 16.85, 20.96, and 29.85 h for small, medium, and large snails at a concentration of 9 mg/L exposure, respectively. Furthermore, as the TS concentration increased or the treatment duration was prolonged, the activities of GSTs and MAO increased, along with the corresponding gene expression levels of PcGSTs1, PcGSTo1, PcmGST1 and PcMAO, compared to those of untreated snails. These results indicated that TS displayed dose- and time-dependent toxicity to P. canaliculata. Overall, the biochemical and molecular results suggested that GSTs and MAO were probably involved in the detoxification metabolism of P. canaliculata against TS. These findings preliminarily clarified the detoxification mechanism of P. canaliculata against TS.